Design and Hydrodynamic Model Test of Mini Submarine Propeller with High Efficiency and Low Cavitation - Mahendra Indiaryanto; Mohammad Ridwan Utina; Nurwidhi Asrowibowo; Siti Sadiah (EPI International Journal of Engineering, 2018)
Design and development of propellers for submarines are in some ways different from propellers for surface vessels. The most important demand is low acoustic signature and propeller efficiency. The design for the propulsor for submarine is a specialist task of a later stage of design. The propulsive efficiency has essensially three parts in the traditional method of approach. The first and major part is the efficiency of the propeller it self as a divice which may develop to overcome the resistance to motion the vessel. The aim of this research is to design a mini submarine propeller and obtain high efficiency and low cavitation. To reach this aim, model tests were performed both in Towing Tank and Cavitation Tunnel. From the propeller model tests, the result shows a good efficiency and low cavitation. Keywords: Submarine , Propeller , Efficiency, Cavitation